Electrophoretic Deposition of Chitosan Coatings Modified with Gelatin Nanospheres To Tune the Release of Antibiotics - Song, Jiankang; Chen, Qiang; Zhang, Yang; Diba, Mani; Kolwijck, Eva; Shao, Jinlong; Jansen, John A; Yang, Fang; Boccaccini, Aldo R; Leeuwenburgh, Sander C. G (ACS applied materials & interfaces, 2016)
Orthopedic and dental implants are increasingly used in the medical field in view of their high success rates. Implant-associated infections, however, still occur and are difficult to treat. To combat these infections, the application of an active coating to the implant surface is advocated as an effective strategy to facilitate sustained release of antibacterial drugs from implant surfaces. Control over this release is, however, still a major challenge. To overcome this problem, we deposited composite coatings composed of a chitosan matrix containing gelatin nanospheres loaded with antibiotics onto stainless steel plates by means of the electrophoretic deposition technique. The gelatin nanospheres were distributed homogeneously throughout the coatings. The surface roughness and wettability of the coatings could be tuned by a simple adjustment of the weight ratio between the gelatin nanospheres and chitosan. Vancomycin and moxifloxacin were released in sustained and burst-type manners, respectively, while the coatings were highly cytocompatible. The antibacterial efficacy of the coatings containing different amounts of antibiotics was tested using a zone of inhibition test against Staphylococcus aureus, which showed that the coatings containing moxifloxacin exhibited an obvious inhibition zone. The coatings containing a high amount of vancomycin were able to kill bacteria in direct contact with the implant surface. These results suggest that the antibacterial capacity of metallic implants can be tuned by orthogonal control over the release of (multiple) antibiotics from electrophoretically deposited composite coatings, which offers a new strategy to prevent orthopedic implant-associated infections.